Spectrophotometric characterization of the Philae landing site and surroundings with the Rosetta/OSIRIS cameras. Issue 1 (5th August 2020) - Hoang, Hong Van; Fornasier, S; Quirico, E; Hasselmann, P H; Barucci, M A; Sierks, H; Tubiana, C; Güttler, C
ABSTRACT: We investigate Abydos, the final landing site of the Philae lander after its eventful landing from the Rosetta spacecraft on comet 67P/Churyumov–Gerasimenko on 2014 November 12. Over 1000 OSIRIS-level 3B images were analysed, which cover the 2014 August–2016 September timeframe, with spatial resolution ranging from 7.6 m pixel −1 to approximately 0.06 m pixel −1 . We found that the Abydos site is as dark as the global 67P nucleus and spectrally red, with an average albedo of 6.5 per cent at 649 nm and a spectral slope value of about 17 per cent/(100 nm) at 50° phase angle. Similar to the whole nucleus, the Abydos site also shows phase reddening but with lower coefficients than other regions of the comet, which may imply a thinner cover of microscopically rough regolith compared to other areas. Seasonal variations, as already noticed for the whole nucleus, were also observed. We identified some potential morphological changes near the landing site implying a total mass-loss of (4.7–7.0) × 10 5 kg. Small spots ranging from 0.1 to 27 m 2 were observed close to Abydos before and after perihelion. Their estimated water ice abundance reaches 30–40 per cent locally, indicating fresh exposures of volatiles. Their lifetime ranges from a few hours up to three months for two pre-perihelion spots. The Abydos surroundings showed a low level of cometary activity compared to other regions of the nucleus. Only a few jets are reported originating nearby Abydos, including a bright outburst that lasted for about 1 h.